Case Report: Tyrosine Kinase Inhibitors Induced Lymphadenopathy in Desmoid Tumor Patients - Papadopoulos, Sotirios; Koulouris, Pantelis; Royer-Chardon, Claire; Tsoumakidou, Georgia; Dolcan, Ana; Cherix, Stephane; Matter, Maurice; Omoumi, Patrick; Digklia, Antonia (Frontiers in Endocrinology, 2022)
Tyrosine kinase inhibitors (TKIs), are nowadays a valuable treatment of desmoid tumors, a rare mesenchymal neoplasm. Although many side effects of imatinib and pazopanib, commonly or rarely occurring, have been described, reactional lymphadenopathy has not yet been reported. In this publication we report two cases of patients with desmoid tumors, treated with pazopanib and imatinib, who developed reactional lymphadenopathy. As this side effect is presented as a newly formed mass, it can result in new diagnostic questions, added imaging tests and can even lead to discontinuation of the treatment. This report may help the clinicians facing similar problems adopt a 'watch and wait' approach.